Evaluation of Nutritional Profile: Proximate Composition, Sensory Attributes, and Energy Content of Otong Soup and Ayan Ekpang Iwa in Traditional Oron Cuisine, Akwa Ibom State - Bassey, Stella Oyom; Effiom, Eteng Ofem; Effanga, Bassey Okon; Sunday, George Ubong; Koofreh, Mary Offiong; Agiang, Margaret (Department of Food Science and Biotechnology, Faculty of Agriculture Technology, Universitas Brawijaya, 2025)
Nigeria’s rich culinary heritage features numerous nutrient-dense soups, yet malnutrition remains a significant concern, particularly in rural areas. This study assessed the proximate composition and caloric content of two traditional dishes commonly consumed in Oron, Akwa Ibom State, Otong Soup and Ayan Ekpang Iwa. Ingredients were sourced from Watt Market, Calabar, and standardized using insights from a focus group discussion. Chemical analysis revealed that Otong Soup (dry weight) contains 35.54±0.06% protein, 23.66±0.06% fat, and 14.4±0.20% carbohydrates, yielding an energy value of 412.7±0.02 kcal. In contrast, Ayan Ekpang Iwa is predominantly carbohydrate-rich (81.93±0.07%, 346.53±1.98 kcal), with moisture content at 76% and dry matter measured at 23.37±0.02%. Its ash content, crude protein, fiber, fat, and carbohydrate levels were 2.26±0.02%, 9.60±0.02%, 1.24±0.00%, 6.39±0.02%, and 3.89±0.06%, respectively, contributing to an energy value of 111.43±0.0 kcal. Sensory evaluation ranked Otong Soup higher in taste (8.35±0.59), texture (8.20±0.90), aroma (8.05±0.76), and color (7.65±1.09 and 8.25±1.02). For Ayan Ekpang Iwa, taste (7.20±0.89) received the highest rating, whereas texture (7.00±1.12) was the lowest. Color also had a relatively high score (7.15±1.31, p<0.05; 7.10±1.12). Findings confirm that both dishes offer valuable nutrients, emphasizing their potential to support dietary improvements.